Upaya Guru Mengembangkan Karakter Berpikir Kritis dan Berpikir Kreatif Siswa Melalui Pembelajaran Matematika - Orin Asdarina; Rahmah Johar; Hajidin Hajidin (Universitas Syiah Kuala, 2019)
The rise of the moral crisis that occurred among students, fuelling disquiet and anxiety of the various elements of the nation. One of the solutions to tackle the problems of the moral crisis is through the character education. This research aims to analyze the efforts of teachers to develop the character of critical thinking and creative thinking of students through the learning of mathematics, and know the relationship of teacher's effort to develop the character of critical thinking and creative thinking characters with student learning outcomes related to the ability of critical thinking and creative thinking. Subjects in the study was a teachers of mathematics class V-2 MIN Tungkop Aceh Besar District. Research data collected through observation and interview against teachers and students as well as through tests the ability of the creative thinking and critical thinking that are given to students. Based on the results of the research it is known that 1) The teacher had been an effort to develop the character of critical thinking and creative thinking of students by providing questions that include critical thinking and creative though not at all meetings, but the encouragement of teachers in order to give students the critical thinking and creative thinking during the learning process still belongs to minimal 2) The ability of critical thinking and creative thinking students of class V – 2 in the category of “Very low”.